Energy-Efficient Spectrum Management for Cognitive Radio Sensor Networks - Ren, Ju.; Zhang, Ning.; Shen, Xuemin (Sherman).; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This monograph addresses the spectrum-scarcity problem by providing a comprehensive overview of spectrum resource management in Cognitive Radio Sensor Networks (CRSNs). It shows a variety of CRSN applications covering Machine-to-Machine communications, cyber physical systems and Internet-of-Things. The authors explore the benefits of an integrated energy efficient spectrum management solution for CRSNs including spectrum sensing, decision and allocation. Both theoretical and experimental aspects of CRSNs are covered in detail. Academics, researchers and developers will find this monograph an exceptional resource with valuable knowledge and insights. It also has extensive references from top journals, conference proceedings, books and standards.
Wireless Sensor Networks -- Cognitive Radio -- Cognitive Radio Sensor Networks -- Applications and Challenges of CRSN -- Arisen Challenges for CRSNs -- Spectrum Resource Management for CRSNs -- Dynamic Spectrum Access Decision -- Secure Collaborative Spectrum Sensing -- Joint Energy Management and Spectrum Resource Allocation -- Dynamic and Energy-Efficient Channel Access in Clustered CRSNs -- Dynamic Channel Access for Intra-Cluster Data Transmission -- Joint Power Allocation and Channel Access for Inter-Cluster Data Transmission -- Secure and Energy-Efficient Collaborative Spectrum Sensing -- Analysis on Trade-off Between Security and Energy-Efficiency -- FastDtec: Trust Evaluation for Fast Compromised Node Identification -- Secure and Energy-Efficient Collaborative Spectrum Sensing -- Joint Channel Allocation and Sampling Rate Control in EH-CRSNs -- System Model and Problem Formulation -- Problem Decomposition and Solution -- Subproblem Solutions -- JASC: Joint Channel Allocation and Sampling Rate Control Scheme -- Concluding Remarks and Future Directions -- Distributed Spectrum Resource Management for Large-Scale CRSNs -- Cross-layer Design for Opportunistic Spectrum Access -- Energy Harvesting and Transfer in CRSNs. .
Keywords: Telecommunication; Electric power production; Computer networks .; Communications Engineering, Networks; Electrical Power Engineering; Mechanical Power Engineering; Computer Communication Networks